Ready to run : unlocking your potential to run naturally - Starrett, Kelly, ....-; Murphy, T. J., ....- (Las Vegas (Nev.) : Victory Belt Publishing, 2014)
Are You Ready to Run? Is there a bridge from the injury-ridden world of the modern runner to the promised land that barefoot running and Born to Run have led us to believe exists? Can we really live the running life free from injury? Is there an approach designed to unlock all the athletic potential that may be hidden within? Can we run faster, longer, and more efficiently? In a direct answer to the modern runner's needs, Dr. Kelly Starrett, author of the bestseller Becoming a Supple Leopard: The Ultimate Guide to Resolving Pain, Preventing Injury, and Optimizing Athletic Performance, has focused his revolutionary movement and mobility philosophy on the injury-plagued world of running. Despite the promises of the growing minimalist-shoe industry and a rush of new ideas on how to transform running technique, more than three out of four runners suffer at least one injury per year. Although we may indeed be “Born to Run,” life in the modern world has trashed and undercut dedicated runners wishing to transform their running. The harsh effects of too much sitting and too much time wearing the wrong shoes has left us shackled to lower back problems, chronic knee injuries, and debilitating foot pain. In this book, you will learn the 12 standards that will prepare your body for a lifetime of top-performance running. You won't just be prepared to run in a minimalist shoe–you'll be Ready to Run, period.
With the proper combination of motor control skills and ranges of motion clicking into place, running will cease to be a joyless, grinding mill for injuries that wreak havoc on your athletic life.
Keywords: Hardlopen